@ your service : how to attract new customers, increase sales, and grow your business using simple customer service techniques - Eliason, Frank, 1972- (Hoboken, N.J. : Wiley, 2012)
'A guide to refocusing your business on those who matter most: customers and employees.Technology and social media tools have made it easier than ever for companies to communicate with consumers. They can listen and join in on conversations, solve problems, get instant feedback about their products and services, and more. So why, then, are most companies not doing this? Instead, is seems as if customer service is at an all time low, and that the few companies who are choosing to focus on their customers are experiencing a great competitive advantage. At Your Service explains the importance of refocusing your business on your customers and your employees, and just how to do it. Explains how to create a culture of empowered employees who understand the value of a great customer experience Advises on the need to communicate that experience to their customers and potential customers Frank Eliason, recognized by BusinessWeek as the'most famous customer service manager in the US, possibly in the world,' has built a reputation for helping large businesses improve the way they connect with customers and enhance their relationships At Your Service will appeal to leaders, managers, business owners, customer service professionals, and anyone who wants to learn how to add value to their organization'--
Includes index.
Keywords: Customer services; Corporate culture; Customer relations